THE USE OF SOCIAL INTERACTIVE WRITING FOR ENGLISH LANGUAGE LEARNERS (SWELL) METHOD TO DEVELOP THE STUDENTS’ ABILITY TO WRITE NARRATIVE TEXT - St Asriati AM (Universitas Muhammadiyah Makassar, 2013)
This research aimed to find out the development of the students’ ability to write narrative text viewed from both generic structure and language use at XI IPA of SMA Muhammadiyah Sungguminasa, Gowa. The type of this research was a Classroom Action Research consisted of two cycles. One cycle consisted of four meetings. Thus, that there were eight meetings for two cycles. This classroom action research was done at XI IPA of SMA Muhammadiyah Sungguminasa, Gowa. The research subjects were the students of class XI in 2012/2013 academic year with 26 students. Those consisted of 10 men and 16 women. The instruments of this research were writing test and observation. The research findings indicated that the Use of SWELL Method could develop the students’ ability to write narrative text viewed from the generic structure and language use. It was proved by the students’ mean score in cycle 2 test result was (77.81) which developed 16.31 % from the cycle 1 mean score (66.98). It was highly developed from a diagnostic test (D – test) mean score (58.69). The students’ development in cycle 2 indicated that it had met the researcher score target (75), and considered to be successful criteria in developing the students’ ability to write narrative text covering generic structure and language use.Keywords: writing, development, social interactive writing